Roles of Geographical Heterogeneity on Income Distribution: Empirical Evidence from Thailand - Kitipacharadechatron, Ronnakron; Phasuk, Padcharee (Thailand and The World Economy, 2025)
Income disparity has led to numerous significant issues, prompting the need for a deeper understanding of its causes and impacts. This paper examines the role of geographical heterogeneity in income distribution, providing empirical evidence to support development theory and inform policymakers in designing effective development policies. Secondary data from government surveys and publicly accessible sources, including satellite data, are utilized to conduct the analysis. The econometric model employs the Generalized Method of Moments (GMM), and spatial patterns are investigated using spatial autocorrelation techniques. The findings indicate substantial regional income disparities in Thailand, particularly in the northern and northeastern regions, where economic activity is considerably lower compared to the central region. Furthermore, the results highlight the significant effect of geographical heterogeneity on income distribution, with agricultural areas exhibiting lower income levels relative to regions concentrated in manufacturing and services. These findings underscore the importance of addressing geographical factors in development planning to reduce income inequality.